Enhancement of Storage Stability, Textural Profile, Physico-Chemical Parameters and Sensory Attributes of Chevon Meatballs by Guava Powder Incorporation - Mahapatra, G.; Biswas, S.; Patra, G.; Vidyarthi, A. K. (International Journal of Bio-resource and Stress Management, 2019)
Guava (Psidium guajava) powder was added to chevon meatball mixture at the rate of 1.0%, 1.5% and 2.0% on w/w basis to evaluate the storage stability, textural parameters, physico-chemical properties of cooked chevon meatballs. The products were stored for a period of 21 days at refrigeration temperature (4±1 °C). Studies indicative of storage stability were conducted on 0, 3, 7, 14 and 21 day rest all studies were conducted on day zero. Six sets of experiments were conducted and each experiment had been replicated four times i.e. n=24. During the 21 days refrigerated storage period, compared to control samples, the guava powder treated samples had significantly lowered (p<0.05) thiobarbituric acid reacting substances values and lower total plate count, total psychrotrophic count, total coliform count and yeast and mould count, thus indicating improved anti-oxidant and microbiological quality. Addition of guava powder to the meatball mixture had significantly reduced (p<0.05) the emulsion stability of the meatball mixture. The final product had significantly (p<0.05) lowered moisture, fat, ash, moisture retention, fat retention and pH. The cooking yield too was significantly reduced (p<0.05) but the meatballs produced had desirable textural properties, improved sensorial characteristics and better acceptability. This study indicated that guava powder could successfully be utilized as additives to meatball mixtures to to produce meatballs having improved shelf-life and and superior functional properties.